If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5n + 2)(3n + -7) = 0 Reorder the terms: (2 + 5n)(3n + -7) = 0 Reorder the terms: (2 + 5n)(-7 + 3n) = 0 Multiply (2 + 5n) * (-7 + 3n) (2(-7 + 3n) + 5n * (-7 + 3n)) = 0 ((-7 * 2 + 3n * 2) + 5n * (-7 + 3n)) = 0 ((-14 + 6n) + 5n * (-7 + 3n)) = 0 (-14 + 6n + (-7 * 5n + 3n * 5n)) = 0 (-14 + 6n + (-35n + 15n2)) = 0 Combine like terms: 6n + -35n = -29n (-14 + -29n + 15n2) = 0 Solving -14 + -29n + 15n2 = 0 Solving for variable 'n'. Factor a trinomial. (-2 + -5n)(7 + -3n) = 0Subproblem 1
Set the factor '(-2 + -5n)' equal to zero and attempt to solve: Simplifying -2 + -5n = 0 Solving -2 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5n = 0 + 2 -5n = 0 + 2 Combine like terms: 0 + 2 = 2 -5n = 2 Divide each side by '-5'. n = -0.4 Simplifying n = -0.4Subproblem 2
Set the factor '(7 + -3n)' equal to zero and attempt to solve: Simplifying 7 + -3n = 0 Solving 7 + -3n = 0 Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3n = 0 + -7 -3n = 0 + -7 Combine like terms: 0 + -7 = -7 -3n = -7 Divide each side by '-3'. n = 2.333333333 Simplifying n = 2.333333333Solution
n = {-0.4, 2.333333333}
| (9-x)(2x^2-4)(9x^3+6x-27)(5x-2)=0 | | .7(x)=7.50 | | 3x^3+2x^2+4=28 | | .7(x)=3.90 | | 7(x)=3.90 | | .7(x)=6 | | .7(x)=5 | | .3(x)=5 | | 5.99x+2.05= | | 3x-11=1-x | | 5(y-2)-y=42 | | 1.3(x)=5 | | 8m-27=28 | | a-4/3=2a+2/3 | | 7x-8+1=8-9+7x | | 3x+1=30 | | 4x-8=6x-16 | | 5x+6z=4+8y | | 40=x-23 | | 5.99x+2.05=8.45 | | 1.62+7n=4n+2.7n | | 13x+18=70 | | 3(u+9)=8u-8 | | x^2-1=2x+4 | | 2(y+5)=18 | | 50(p+20)=20(p+10) | | 10w=4000 | | -7x-3x+2=-8+8 | | x+5sqrt(x)-14=0 | | 2(3y+1)=14+3y | | (4a^2+9b^5)-(-2a^2-6b^5)= | | 18-6k=-7(2+2k) |